Thermally conductive articles containing entangled or aligned fibers, methods for manufacturing the same, and battery modules

JP2026174736APending Publication Date: 2026-10-303M INNOVATIVE PROPERTIES CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026091723
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-03-03
Filing Date
2026-06-01
Publication Date
2026-10-30

Smart Images

  • Figure 2026174736000001_ABST
    Figure 2026174736000001_ABST
Patent Text Reader

Abstract

The present invention provides a thermally conductive article having advantageous properties of thermal conductivity and compressibility, and a method for preparing the same. [Solution] A thermal conductive article 1000 includes a pad having a first main surface and a second opposite main surface, and a thickness between the main surfaces, wherein the thickness is formed of entangled thermal conductive fibers, and at least a portion of the entangled thermal conductive fibers has at least one end on the first opposite main surface, the opposite second main surface, or both. The pad is at least partially impregnated with a polymer. Another thermal conductive article includes a pad having a first main surface and a second opposite main surface, and a thickness between them, a first thermal conductive skin layer and a second thermal conductive skin layer. The thickness of the pad is formed of aligned thermal conductive fibers, and at least a portion of the thermal conductive fibers has ends on the first opposite main surface and the opposite second main surface.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] Batteries can generate a significant amount of heat during charging and discharging, and the temperature needs to be controlled to prevent thermal runaway or performance degradation. A thermal interface material (TIM) functions as a thermal bridge between the battery and the cooling system to dissipate heat from the battery to the cooling system. The form factor of the TIM can vary, but most commonly it includes an organic matrix (e.g., acrylic, silicone, epoxy, oil) and thermally conductive filler particles (e.g., ceramic, carbon, or metal particles). In such cases, the thermally conductive particles are randomly distributed within the organic matrix, which functions as a binder and greatly influences the determination of the final mechanical properties of the TIM.

Brief Description of the Drawings

[0002] [Figure 1A] FIG. 2 is a schematic top view of a nonwoven web for use in making exemplary articles that can be prepared according to the present disclosure.

[0003] [Figure 1B] FIG. 2 is a schematic side view of the nonwoven web of FIG. 1A.

[0004] [Figure 1C] FIG. 3 is a perspective view of a swirling member for use in making exemplary articles that can be prepared according to the present disclosure.

[0005] [Figure 1D] FIG. 4 is a perspective view of an exemplary article according to the present disclosure.

[0006] [Figure 1E] FIG. 5 is a schematic top view of another exemplary article that can be prepared according to the present disclosure.

[0007] [Figure 2] FIG. 6 is a schematic side view of interlaced continuous fibers of an exemplary article that can be prepared according to the present disclosure.

[0008] [Figure 3] This is an optical micrograph showing a side surface of a further exemplary article adjustable according to the present disclosure.

[0009] [Figure 4A] This is an optical micrograph showing a top surface of an additional exemplary article adjustable according to the present disclosure.

[0010] [Figure 4B] This is an optical micrograph showing the top surface of a comparative article.

[0011] [Figure 5] This is a schematic side view of still another exemplary article adjustable according to the present disclosure.

[0012] [Figure 6] This is a schematic side view of a further exemplary article adjustable according to the present disclosure.

[0013] [Figure 7] This is a schematic top view of an exemplary article including an array of pads, adjustable according to the present disclosure.

[0014] [Figure 8] This is a schematic side view of an additional exemplary article adjustable according to the present disclosure.

[0015] [Figure 9A] This is a photograph of another exemplary article prepared according to the present disclosure.

[0016] [Figure 9B] This is a photograph of the side surface of the article of Figure 9A.

[0017] [Figure 10A] This is a photograph of the side surface of a further exemplary article prepared according to the present disclosure.

[0018] [Figure 10B] This is a side photograph of the article of Figure 10A after being compressed with a vise.

[0019] [Figure 10C] FIG. 2 is a schematic side view of a further exemplary article that can be adjusted according to the present disclosure.

[0020] [Figure 11] FIG. 2 is a flowchart of an exemplary method for making a thermally conductive article.

[0021] [Figure 12] FIG. 2 is a flowchart of another exemplary method for making a thermally conductive article.

[0022] [Figure 13] FIG. 2 is a schematic cross-sectional view of an exemplary battery module that can be adjusted according to the present disclosure.

[0023] Where reference characters are used repeatedly in the specification and drawings, they are intended to represent the same or similar features or elements of the present disclosure. It should be understood by those skilled in the art that many other modifications and embodiments can be devised, which fall within the scope and spirit of the principles of the present disclosure. The figures may not be drawn to scale. [Mode for Carrying Out the Invention]

[0024] Thermal management plays an important role in many electronics applications, such as electric vehicle (EV) battery assemblies, power electronics, electronic packaging, LEDs, solar cells, and electrical grids. Certain thermally conductive materials (e.g., adhesives) can be attractive options in these applications due to their ability to efficiently dissipate heat, while having good electrical insulation, feasibility in processing for integrated components or complex geometries, good conformability / wettability to different surfaces, especially good adhesion to different substrates in the assembly.

[0025] Regarding applications in EV battery assemblies, one such application currently utilizing thermally conductive materials is gap filler applications. Generally, requirements for gap filler applications include thermal interface materials (TIMs) having high thermal conductivity, low density, and high compressibility. However, to achieve high thermal conductivity, typically large amounts of inorganic thermally conductive fillers are added to the composition. However, large amounts of thermally conductive fillers adversely affect density, compressibility, and toughness. The thermally conductive articles according to this disclosure advantageously utilize substantially aligned thermally conductive fibers such as copper, aluminum, or graphite. In some embodiments, the thermally conductive articles also include appropriate amounts of voids (i.e., void volume fraction or void volume percentage) in appropriate locations to simultaneously achieve high effective thermal conductivity and compressibility.

[0026] The terms "a," "an," "the," "at least one," and "one or more" are interchangeable.

[0027] The term "and / or" means either one or both. For example, the expression A and / or B refers to A only, B only, or both A and B.

[0028] The term "essentially" means 95% or more.

[0029] The term "rotation" means something that is wrapped around itself, such as a Swiss roll or a roll of tape.

[0030] The terms "curing" and "curability" typically refer to the formation of a network polymer by linking polymer chains through chemical covalent bonds via crosslinkable molecules or groups. Therefore, in this disclosure, the terms "curing" and "crosslinking" may be used interchangeably. Cured polymers or crosslinked polymers are generally characterized by insolubility, but may become swollen in the presence of a suitable solvent.

[0031] In relation to fibers, the term "entangled" means that multiple fibers are interconnected with each other in a meandering manner (e.g., randomly, either as a nonwoven or as a woven or knitted fabric). The fibers are not necessarily fused (e.g., melted) or bonded together; rather, the interconnection of the fibers is essentially made possible by the flexibility of the fibers, which is determined by the fiber composition, denier, crimp index, and other properties, resulting in a significant increase in the strength of the resulting web containing such entangled fibers.

[0032] It was unexpectedly discovered that it is possible to prepare thermally conductive articles that offer advantageous properties of thermal conductivity and compressibility.

[0033] In a first embodiment, a thermally conductive article is provided. The thermally conductive article includes a pad having first and second oppositely oriented main surfaces and a thickness between them, the thickness being formed of a plurality of entangled thermally conductive fibers, at least a portion of which have at least one end on the first oppositely oriented main surface, the oppositely oriented second main surface, or both, and the pad is at least partially impregnated with a polymer.

[0034] In a second aspect, a method for manufacturing a thermally conductive article is provided. This method for manufacturing a thermally conductive article is: a) Obtaining at least one nonwoven web comprising a plurality of entangled thermally conductive fibers and having a first main surface and a second main surface facing the opposite direction, b) Impregnating at least one nonwoven web with a polymer composition or polymerizable composition, c) Drying the polymer composition or polymerizing the polymerizable composition, d1) Wrapping the first main surface of the nonwoven web around the second main surface of the nonwoven web to form an elongated spiral member having a first end and a second end on the opposite side, and e1) Cutting a thin pad from the first end of an elongated rotating member, or d2) Bonding together laminates of multiple coated nonwoven webs, and e2) cutting a thin pad from a first end of a laminate of multiple nonwoven webs,

[0035] This forms a thermal conductive article comprising a pad having first and second oppositely oriented main surfaces and a thickness between them, wherein the thickness is formed of a plurality of entangled thermal conductive fibers, at least a portion of which has at least one end on the first oppositely oriented main surface, the oppositely oriented second main surface, or both, and the pad is at least partially impregnated with a polymer.

[0036] The following disclosures relate to both the first and second aspects.

[0037] A thermally conductive article of a first aspect of this disclosure comprises an entangled fiber (e.g., nonwoven) web that functions as a self-supporting skeleton, with a polymer playing a role in at least partially bonding the thermally conductive fibers to one another, contributing to the mechanical properties of the article. As a result, a continuous thermal path exists through the thickness of the pad (e.g., in the shortest axis, the z-axis direction, also referred to herein as the thickness direction), achieving similar thermal conductivity values ​​while allowing the use of far less thermally conductive material than conventional thermally conductive composite articles. Furthermore, air bubbles may be incorporated into the thermally conductive article during processing, which can become an important component of the final pad, contributing to the observed very low density and high compressibility. Thus, in contrast to conventional TIMs, low density, conformability, and high thermal conductivity can all be achieved in a single solution. In this specification, in this first aspect, it has been found that a favorable combination of thermal conductivity, compressibility, and compression strain recovery (also referred to herein as springback) of an article (e.g., a thermal conductive pad) can be achieved by combining design elements of (i) confluence (e.g., random confluence) and voids of thermal conductive fibers within the thickness of the article, and (ii) design elements of the ends of thermal conductive fibers on one or both main surfaces of the article (e.g., the article includes, for at least some thermal conductive fibers, the respective first and second thermal conductive fiber ends on the first and second main surfaces of the article). The article may also be at least partially impregnated with a polymer. At least partially impregnating with a polymer means that at least a portion of the spaces between thermal conductive fibers are occupied by the polymer. Examples of at least a portion of the space between thermal conductive fibers being occupied by polymers include polymer coatings applied to thermal conductive fibers, polymers located at the bonding points (also referred to herein as contact points) between thermal conductive fibers, and polymers existing as inclusions filling at least a portion of the spaces between thermal conductive fibers. In some embodiments of the first aspect, an article (e.g., a thermal conductive pad) is impregnated with a polymer in the form of a polymer coating applied to thermal conductive fibers, where the polymer is located at the bonding points between thermal conductive fibers.The aforementioned forms of articles containing thermally conductive fibers and impregnated with a polymer within the article's thickness are not inconsistent with the presence of voids within the article's thickness. In other words, the article of the first embodiment may contain the impregnating polymer and voids within the article's thickness, along with the entangled (e.g., randomly entangled) thermally conductive fibers within the thickness. In fact, it is preferable that these three elements coexist, along with the ends of the thermally conductive fibers located on the main surface of the article.

[0038] Referring to Figure 1, a schematic top view of a nonwoven web 100a for use in the production of an exemplary article containing multiple entangled thermal conductive fibers 110 is shown. In this top view, the fibers can be seen along the x-axis (length direction) and y-axis (width direction). Figure 1B shows a schematic side view of the nonwoven web 100a of Figure 1A containing the entangled thermal conductive fibers 110. In this side view, the fibers can be seen along the x-axis (length direction) and z-axis (height direction). Considering that the fibers of a nonwoven web tend to have a predominantly preferred in-plane (e.g., xy-plane) orientation despite being randomly oriented in the plane, a method has been established to reorient the fibers through the plane of the finished article (e.g., a thermal conductive pad) to achieve the thermal benefits of the thermal conductive fibers. This was achieved by one of two different techniques. In the first technique, the procedure begins by winding an entangled thermally conductive fiber web (e.g., a nonwoven web) into a roll, and then thinning the resulting roll to a desired thickness at an angle (e.g., 90 degrees) with respect to the roll axis, thereby obtaining an article having fibers oriented in a plane, in a plane, and at various angles between them, which is beneficial in terms of fiber-to-fiber connectivity and a continuous network from top to bottom. In the second technique, the procedure begins by bonding together a laminate of entangled thermally conductive fiber webs (e.g., a nonwoven web), and then thinly cutting a thermally conductive pad from the first end of the web laminate, the pad having a striped structure obtained from the original web laminate.

[0039] Referring to Figure 1C, a spiral member 100b for use in making an exemplary article is shown with respect to the first art. The spiral member 100b was prepared by rolling a nonwoven web of thermally conductive fibers 110, which had at least partially impregnated with polymer. Figure 1D is a perspective view of the exemplary article 100c after a thin pad has been cut from the spiral member 100b of Figure 1C. In a selected embodiment according to the first art, the pad is a spiral layer.

[0040] Advantageously, in such a method of forming a thermally conductive article, at least a portion of the entangled thermally conductive fibers consequently have ends located on at least one of a first opposite-facing main surface or a second opposite-facing main surface. For example, Figure 1E is a schematic top view of an exemplary article 1000 obtained from the first art, having a coiled nonwoven web 1100 and a plurality of ends 1200 of thermally conductive fibers shown on one main surface of the article 1000. In a selected embodiment, one or both of the first and second opposite-facing main surfaces have a surface density of at least 5, at least 7, at least 10, at least 15, or at least 20 thermally conductive fiber ends per square millimeter, for example, the fiber ends 1200 shown in area 1300 of the article 1000 in Figure 1E. While there are no limitations on the maximum surface density of fiber ends, the main surface or surface of an article according to the Disclosure, including the first embodiment, may have up to 100 thermally conductive fiber ends per square millimeter, e.g., fiber ends 1200 shown in area 1300 of article 1000 in Figure 1E or fiber ends 5200 shown in area 5400 of article 5000 in Figure 5. In some embodiments, the first main surface or the second main surface of an article (e.g., a thermally conductive pad), or both the first and second main surfaces, may have a surface density of fiber ends, e.g., 1 to 100 per square millimeter, in some embodiments 5 to 50 per square millimeter, and in yet other embodiments 7 to 20 per square millimeter, e.g., fiber ends 1200 shown in area 1300 of article 1000 in Figure 1E. Preferably, at least a portion of the thermally conductive fibers have ends on each of the first opposite main surface and the second opposite main surface of the pad. In some embodiments, at least 25%, at least 30%, at least 35%, or at least 40%, and up to 75%, of the thermally conductive fibers have terminations on each of the first opposite-facing main surface and the second opposite-facing main surface of the pad.

[0041] Referring to Figure 2, a schematic side view of entangled fibers 2200 of an exemplary article 2000 is shown, with a portion of the ends 2250 of the thermally conductive fibers located on one or both of the opposing main surfaces of the article 2000. At least some of the fibers provide a continuous heat conduction path from one main surface of the pad to the opposite main surface of the pad, provided by a single thermally conductive fiber. At least some of the fibers provide a connected path of two fibers in contact with each other to achieve a heat conduction path from one main surface of the pad to the opposite surface of the pad. The thermally conductive fibers may take a winding path between the opposing main surfaces of the pad, as seen, for example, in Figure 2. In some embodiments of the thermally conductive articles described herein, both a continuous heat conduction path and a connected heat conduction path are provided from one main surface of the pad to the opposite main surface of the pad. In selected embodiments, only a continuous heat conduction path is provided from one main surface of the pad to the opposite main surface of the pad.

[0042] Referring to Figure 3, an optical microscope photograph is shown showing a side view of an exemplary article 3000 containing multiple continuous thermal conductive fibers 3200. Figure 3 illustrates how diverse the orientations and angles of the individual thermal conductive articles are relative to each other.

[0043] Figure 4A is an optical microscope image showing the top surface of exemplary article 4000, where numerous thermally conductive fibers terminate at the top of the main surface, one set of which is shown as fiber end 4250. Over a 3.4 square millimeter inspection area, 34 ends were observed (i.e., a surface density of 10 fiber ends per square millimeter). In contrast, Figure 4B is an optical microscope image showing the top surface of a comparative article containing a nonwoven web having a structure similar to that of Figure 1A. In Figure 4B, due to a preferred in-plane fiber orientation, there are no fibers terminating at the top of the main surface of the nonwoven web.

[0044] With respect to the second art, Figure 5 is a schematic top view of an exemplary article 5000 having a striped structure including a band 5300 of a nonwoven web 5100, with a plurality of thermal conductive fiber ends 5200 shown on one main surface of the article 5000. In selected embodiments, one or both of the first and second oppositely oriented main surfaces have a surface density of at least 5, at least 7, at least 10, at least 15, or at least 20 thermal conductive fiber ends per square millimeter. While there is no limit to the maximum surface density of fiber ends, a main surface or surface of an article according to the Disclosure, including the first embodiment, may have up to 100 thermal conductive fiber ends, such as the fiber ends 5200 shown within area 5400 of the article 5000 in Figure 5, per square millimeter. In some embodiments, the first main surface or the second main surface of the article (e.g., a thermal conductive pad), or both the first and second main surfaces, have a surface density of 1 to 100 fiber ends per square millimeter, 5 to 50 per square millimeter in some embodiments, and 7 to 20 per square millimeter in yet other embodiments, for example, the fiber ends 5200 shown in area 5400 of article 5000 in Figure 5. Preferably, at least a portion of the thermal conductive fibers have ends on each of the first opposite main surface and the opposite second main surface of the pad. In some embodiments, at least 25%, at least 30%, at least 35%, or at least 40%, and up to 75%, of the thermal conductive fibers have ends on each of the first opposite main surface and the opposite second main surface of the pad.

[0045] Referring to Figure 6, a schematic side view of exemplary article 6000 is shown, which can be prepared by the second technique described above, in which a laminate of nonwoven webs is bonded together and a pad is thinly sliced ​​from a first end of the laminate of nonwoven webs. Article 6000 comprises a plurality of interconnected thermal conductive strips 6050, each strip characterized by the respective total number of thermal conductive fibers, as determined by the respective nonwoven webs laminated before the pad is thinly sliced ​​from the laminate of nonwoven webs. Typically, the nonwoven webs have a structure similar to that of Figure 1A, and therefore, when laminated and thinly sliced ​​at the end of the laminate, provide a pad with several thermal conductive fibers oriented parallel to the thickness direction (e.g., the z-axis) of the pad, with a plurality of nonwoven ends essentially standing upright.

[0046] In the embodiment shown in Figure 6, article 6000 further comprises an optional first skin layer 6250 attached to a first main surface of the attached pad 6050, and an optional second skin layer 6350 attached to a second main surface of the attached pad 6050. Each of the first skin layer 6250 and the second skin layer 6350 of article 6000 is a composite material comprising a polymer and at least one thermally conductive particle 6260 and 6360, respectively. Any thermally conductive article described herein, for example, an article in which the pad is a spiral layer, may also incorporate one or more such skin layers. In some embodiments including skin layers, the pad includes at least several thermally conductive fibers extending into the first skin layer, at least several thermally conductive fibers extending into the second skin layer, or both (not shown). In some embodiments including a skin layer, the pad includes at least several thermally conductive fibers (not shown) whose first ends extend into the first skin layer and whose second ends extend into the second skin layer. In yet another embodiment including a skin layer, the pad includes at least several thermally conductive fibers extending completely through the first skin layer until reaching the first main surface of the pad, at least several thermally conductive fibers extending completely through the second skin layer until reaching the second main surface of the pad, or both. In yet another embodiment including a skin layer, the pad includes at least several thermally conductive fibers extending completely through the first skin layer until reaching the first main surface of the pad and whose second ends extend completely through the second skin layer until reaching the second main surface of the pad, so that such a pad provides a continuous heat conduction path from the first main surface to the second main surface. In some embodiments that do not include an optional skin layer, the pad includes thermally conductive fibers (not shown) whose first ends extend to reach a first main surface of the pad and whose second ends extend to reach a second main surface of the pad, so that such a pad provides a continuous heat conduction path from the first main surface to the second main surface.

[0047] Optionally, the thermal conductive article includes an array of pads. For example, Figure 7 is a schematic top view of an array of pads arranged in a tile-like manner, each in the form of a spiral layer 7300, to form a thermal conductive article 7000. The array of pads may take any shape, with open spaces between the spiral layers, or the spiral layers may be compressed in-plane to fill all the gaps between the pads and form a complete sheet. Alternatively, the pads may take the form of a laminate of nonwoven webs, as shown in Figure 6, or some combination of pad structures.

[0048] Advantageously, the thermally conductive articles according to this disclosure are low-density articles, which means that less material input is required than for high-density articles. Thermally conductive articles typically exhibit densities of less than 1.00 g (g / cc) per cubic centimeter, 0.90 g / cc or less, 0.80 g / cc or less, 0.70 g / cc or less, 0.60 g / cc or less, 0.50 g / cc or less, 0.40 g / cc or less, 0.30 g / cc or less, or 0.20 g / cc or less, and 0.05 g / cc or greater. One factor that makes such low-density thermally conductive articles possible is the presence of a considerable amount of void volume (e.g., containing ambient air or a selected gas) throughout the pad or within the thickness of the pad (e.g., between skin layers, if present). In any embodiment, with respect to the thickness of the pad (e.g., between skin layers, if present, or over the entire cross-section of the pad), the pad may have a void volume fraction of at least 10%, at least 20%, at least 30%, at least 40%, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 92%, at least 95%, or at least 97%, and less than 100%. In some embodiments, with respect to the thickness of the pad (e.g., between skin layers, if present, or over the entire cross-section of the pad), the pad may have a void volume fraction of 10% to 97%, 50% to 95%, or 70% to 92%.

[0049] The thickness of a thermally conductive pad is not particularly limited and is usually selected based on the size gap that needs to be filled for the specific application of the article. Typically, pad thicknesses are 0.1 mm or more, 0.25 mm or more, 0.50 mm or more, 0.75 mm or more, 1.0 mm or more, 1.5 mm or more, 2.0 mm or more, 2.5 mm or more, 5.0 mm or more, 10.0 mm or more, or 15.0 mm or more, and 50 mm or less, 45 mm or less, 40 mm or less, 35 mm or less, 30 mm or less, 25 mm or less, or 20 mm or less.

[0050] A thermally conductive article preferably exhibits a thermal conductivity in the thickness direction (e.g., pad thickness) of greater than 0.5 W / mK, 1 W / mK, 2 W / mK or more, 3 W / mK or more, 4 W / mK or more, 5 W / mK or more, 6 W / mK or more, 7 W / mK or more, or 8 W / mK or more. A thermally conductive article often preferably exhibits the maximum thermal conductivity, but typically exhibits a thermal conductivity in the thickness direction (e.g., pad thickness) of 25 W / mK or less, 22 W / mK or less, 20 W / mK or less, 18 W / mK or less, 16 W / mK or less, 14 W / mK or less, 12 W / mK or less, or 10 W / mK or less. In some embodiments, the thermally conductive article exhibits a thermal conductivity in the thickness direction (e.g., pad thickness) of 0.5 to 25 W / mK, 1 to 15 W / mK in some embodiments, and 2 to 10 W / mK in some embodiments.

[0051] Compressibility can be a useful feature of the thermal conductive articles according to this disclosure. This is partly due to variations in the thickness of the gap that needs to be filled by the thermal conductive article, and / or partly due to changes in the thickness of the gap during use of the thermal conductive article. In some embodiments, the thermal conductive articles preferably exhibit compression of 30% or more, 40% or more, 50% or more, 60% or more, or 70% or more at a maximum pressure of 2 megapascals (MPa), and compression of 80% or less at a maximum pressure of 2 MPa.

[0052] The thermally conductive fibers for use in the articles of this disclosure are not particularly limited. Suitable materials for the thermally conductive fibers include, but are not limited to, copper, aluminum, steel, aluminum-clad steel, iron, bronze, brass, nickel, chromium, gold, platinum, silver, palladium, rhodium, iridium, ruthenium, osmium, carbon, graphite, aluminum oxide, silicon carbide, boron nitride, ultra-high molecular weight polyethylene, metal-clad polymer fibers, thermally conductive particle-filled polymer fibers, or combinations thereof. Typically, the thermally conductive fibers have a thermal conductivity of 5 W / mK or higher. In some embodiments, the thermally conductive fibers are metals.

[0053] Nonwoven webs can be made from a wide range of fiber types, including blends of polymer and inorganic fibers to control the thermal conductivity and mechanical properties of the web. Optionally, the pad further comprises multiple second fibers entangled with the thermal conductive fibers. In some embodiments, the thermal conductive fibers are metallic (e.g., copper, aluminum, steel, nickel, silver, or metal-coated polymer fibers), and the second fibers are polymer or ceramic. Suitable polymer fibers include, but are not limited to, at least one of polyolefin fibers (e.g., polyethylene or polypropylene), polyester fibers, or polyamide fibers. Furthermore, phenolic (e.g., thermosetting) fibers may be suitable polymer fibers and may be useful as curing and / or springback additives for thermal conductive articles subjected to high levels of compression.

[0054] The polymer impregnating the pad at least partially may be selected to provide effective bonding of the thermally conductive fibers. In many embodiments, the polymer has a glass transition temperature (T) of less than 20°C. g) has. Suitable polymers include, but are not limited to, silicones, rubbers, polyolefins, and acrylates. Typically, the polymer is present as a coating on at least a portion of the entangled thermal conductive fibers. The web may further include a plurality of thermal conductive particles dispersed within the polymer to increase the thermal conductivity of the article. Suitable thermal conductive particles are described in detail below with respect to an optional skin layer. The thermal conductive article may optionally be further impregnated with a second polymer which differs from the first polymer and may be selected to impart one or more different properties to the final article, such as adhesion to other materials, springback / mechanical response, etc. For example, in one embodiment, the first polymer may be used to bond the thermal conductive fibers together, the second polymer may be used to impart springback, and in addition, optionally one of the polymers may contain thermal conductive particles and / or flame retardant material.

[0055] Fiber dimensions can be modified to adjust the cohesiveness of the web and aid in processing. Preferred fiber lengths include average lengths of 0.1 cm or more, 0.2 cm or more, 0.3 cm or more, 0.4 cm or more, 0.5 cm or more, 0.6 cm or more, 0.7 cm or more, 0.8 cm or more, 0.9 cm or more, 1 cm or more, 2 cm or more, 3 cm or more, or 4 cm or more, and average lengths of 10 cm or less, 9 cm or less, 8 cm or less, 7 cm or less, 6 cm or less, or 5 cm or less. In most cases, thermally conductive fibers have an average diameter of 0.5 micrometers or more, 1 micrometer or more, 2 micrometers or more, 5 micrometers or more, 7 micrometers or more, 10 micrometers or more, 12 micrometers or more, 15 micrometers or more, 20 micrometers or more, 25 micrometers or more, 30 micrometers or more, 40 micrometers or more, 50 micrometers or more, 60 micrometers or more, 70 micrometers or more, 80 micrometers or more, or 90 micrometers or more, and an average diameter of 250 micrometers or less, 225 micrometers or less, 200 micrometers or less, 175 micrometers or less, 150 micrometers or less, 125 micrometers or less, or 100 micrometers or less. The term "diameter" in relation to fibers refers to the average length of the maximum dimension of the fiber cross-section. For example, for a fiber with a rectangular cross-section, the diameter is the longest measurable distance along that cross-section. The average diameter and average length can be determined by visually examining the diameter and length of 25 or more individual fibers under a microscope.

[0056] Referring to Figure 11, a flowchart of an exemplary method for producing a thermally conductive article is shown. More specifically, Figure 11 includes the steps of: obtaining at least one nonwoven web comprising a plurality of entangled thermally conductive fibers and having a first main surface and a second main surface facing the opposite direction; impregnating at least one nonwoven web with a polymer composition or a polymerizable composition; drying the polymer composition or polymerizing the polymerizable composition; and either wrapping the first main surface of the nonwoven web around the second main surface of the nonwoven web to form an elongated spiral member having a first end and a second end facing the opposite side, and cutting a thin pad from the first end of the elongated spiral member, or bonding a laminate of a plurality of coated nonwoven webs together, and cutting a thin pad from the first end of the laminate of the plurality of nonwoven webs, or either step 1140b bonding a laminate of a plurality of coated nonwoven webs together, and cutting a thin pad from the first end of the laminate of the plurality of nonwoven webs, or step 1150b. This method optionally further includes impregnating a nonwoven web(s) with a second polymer before forming an elongated spiral member, for example, in step d1 or step 1140a.

[0057] Obtaining a nonwoven web may optionally involve using any suitable web-forming process that utilizes thermally conductive fibers. Suitable web-forming processes may include, but are not limited to, air-laid, wet-laid, carding, melt-spinning, melt-blown, and stitch-bond methods. In some embodiments, the nonwoven web may be created by air-laiding short fibers (for example, by using a so-called Rando Webber apparatus commercially available from Rando Machine Corporation (Macedon, NY)).

[0058] In some embodiments, a large quantity of thermally conductive fibers collected in the web forming process may be processed in any preferred manner to bond at least some of the fibers of the web to other fibers of the web. In certain embodiments, such fibers may include at least some bonding fibers, in which case at least some of the fibers can be bonded by applying heat to the fiber aggregate (either by passing the fiber aggregate in a furnace or on a hot roll, or by subjecting the fiber aggregate to a so-called through-air bonding), followed by cooling. In such cases, it may be advantageous to heat the fibers to a temperature close to or above the melting point of the bonding fibers, but lower than the melting point of the (first) thermally conductive fibers, in order to perform such bonding operations. Care should be taken to avoid causing large-scale melting of the fibers and / or collapse of the fiber structure of the nonwoven web. The nonwoven web has sufficient mechanical strength and integrity to be treated as a self-supporting fiber web or pad.

[0059] In many cases, the polymer composition or polymerizable composition contains a low solids content composition when applied to the thermal conductive fibers of a nonwoven web. The composition is then dried or cured to essentially remove all of the solvent in the composition, yielding the polymer. For example, the polymer composition or polymerizable composition may contain 2% by weight (Wt) or more solids, 3% by weight or more solids, 4% by weight or more solids, 5% by weight or more solids, 6% by weight or more solids, 7% by weight or more solids, 8% by weight or more solids, 9% by weight or more solids, and based on the total weight of the solvent and polymer and polymerizable components in the polymer composition or the polymerizable composition, it may contain 15% by weight or less solids, 14% by weight or less solids, 13% by weight or less solids, 12% by weight or less solids, 11% by weight or less solids, or 10% by weight or less solids. For example, this solids content does not include the thermal conductive particles contained in the polymer composition or polymerizable composition.

[0060] In some embodiments, the method further includes attaching a first skin layer to a first main surface of the pad, and optionally attaching a second skin layer to a second main surface of the pad. The thermal conductive article may further include a first skin layer attached to the first main surface of the pad. Similarly, the thermal conductive article may further include a second skin layer attached to the second main surface of the pad. Advantageously, one or both of the optional skin layers may function as an adhesive layer, a fiber sealing layer, a surface wetting layer, or a combination thereof. One or more skin layers and thermal conductive fibers (e.g., ends of thermal conductive fibers) may penetrate each other. Furthermore, the thermal conductive fibers (e.g., ends of thermal conductive fibers) may penetrate one or more skin layers so that they appear on one or both main surfaces of the article (e.g., a thermal conductive pad), and the main surface or surface of the article is partially defined by one or more skin layers. Alternatively, the thermally conductive fibers (e.g., the ends of the thermally conductive fibers) may protrude beyond one or more skin layers so as to appear on one or both of the main surfaces of the article (e.g., a thermally conductive pad), and the main surface or surface of the article may be partially defined by one or more skin layers.

[0061] Some suitable polymers for the skin layer include silicones, acrylates, polyurethanes, elastomers, and rubbers. In some embodiments, hot-meltable pressure-sensitive adhesive compositions are preferred, such as acrylic adhesives, polyalphaolefin adhesives, rubber-based adhesives, silicone adhesives, blends of rubber-based and acrylic adhesives, and combinations thereof, having a number average molecular weight of 25,000, as described in U.S. Patent No. 7,229,683 (Fischer et al.). Furthermore, suitable acrylates include, but are not limited to, acrylic polymer components as described in U.S. Patent No. 7,851,534 (Yoda et al.), U.S. Patent Publication No. 2011 / 0245373 (Yoda), EP Publication No. 0566093 (Webb et al.), and / or U.S. Publication No. 2011 / 0031435 (Yoda et al.). Suitable silicones include, for example, organopolysiloxanes as described in U.S. Patent Application Publication No. 2019 / 0292349 (Ito). Suitable two-component polymers, such as silicone gels or urethane resins, as well as synthetic rubber resins and acrylic thermoplastic resins, include those described in U.S. Patent No. 6,794,030 (Okada et al.).

[0062] In some embodiments, the skin layer contains thermally conductive particles distributed within the layer. Generally, any known thermally conductive filler can be used, but electrically insulating fillers may be preferred if breakthrough voltage is a concern. Suitable electrically insulating thermally conductive fillers include ceramics such as oxides, hydroxides, oxyhydroxides, silicates, borides, carbides, and nitrides. Suitable ceramic fillers include, for example, silicon oxide, zinc oxide, aluminum oxide, aluminum hydroxide, aluminum trihydrate (ATH), boron nitride (e.g., hexagonal boron nitride), silicon carbide, and beryllium oxide. Other thermally conductive fillers include carbon-based materials such as carbon nanotubes, graphene, and graphite, as well as metals such as aluminum and copper. The thermal conductivity of some representative inorganic materials is listed in the table below. [Table 1]

[0063] In some embodiments, the thermally conductive particles include unground aluminum hydroxide particles obtained by crystallization, as described, for example, in U.S. Patent Application Publication 2011 / 0245373 (Yoda). In some embodiments, the thermally conductive particles include a mixture of boron nitride particles, as described, for example, in U.S. Patent Application Publication 2018 / 0215964 (Wieneke et al.). In some embodiments, the thermally conductive particles include a mixture of aluminum nitride particles and ground aluminum oxide particles, as described, for example, in U.S. Patent Application Publication 2019 / 0292349 (Ito). In some embodiments, the thermally conductive particles include a mixture of metal oxide and metal hydroxide (e.g., aluminum hydroxide or aluminum oxide mixed with magnesium hydroxide), as described, for example, in U.S. Patent No. 7,851,534 (Yeda et al.). In some embodiments, the thermally conductive particles include a mixture of silicon carbide particles having a large particle size and boron nitride particles having a small particle size, as described, for example, in U.S. Patent No. 6,794,030 (Okada et al.).

[0064] In some embodiments, suitable thermal conductive particles include a material having a bulk thermal conductivity of at least 15 or 20 W / mK. In other embodiments, the thermal conductive particles include a material having a bulk thermal conductivity of at least 25 or 30 W / mK. In yet another embodiment, the thermal conductive particles include a material having a bulk thermal conductivity of at least 50, 75, or 100 W / mK. In yet another embodiment, the thermal conductive particles include a material having a bulk thermal conductivity of at least 150 W / mK. In a typical embodiment, the thermal conductive particles include a material having a bulk thermal conductivity of about 350 or 300 W / mK or less.

[0065] Thermally conductive particles are optionally present in the polymer composition or polymerizable composition in amounts of 40% or more by weight, 45% or more by weight, 50% or more by weight, 55% or more by weight, 60% or more by weight, 65% or more by weight, 70% or more by weight, 75% or more by weight, or 80% or more by weight based on the total weight of the polymer composition or polymerizable composition, and 95% or less by weight, 90% or less by weight based on the total weight of the polymer composition or polymerizable composition, or 85% or less by weight based on the total weight of the polymer composition or polymerizable composition.

[0066] In some embodiments, the thermally conductive particles are present in amounts of 30 volume% or more, 35 volume% or more, 40 volume% or more, 45 volume% or more, or 50 volume% or more, based on the total volume of the polymer composition or polymerizable composition, and 70 volume% or less, 65 volume% or less, 60 volume% or less, based on the total volume of the polymer composition or polymerizable composition, or 55 volume% or less, based on the polymer composition or polymerizable composition.

[0067] Thermally conductive particles are available in many shapes, such as spherical, irregular, plate-like, and needle-like. In certain applications, through-plane thermal conductivity may be important. Therefore, in some embodiments, generally symmetrical (e.g., spherical or hemispherical) fillers may be used. In some embodiments, the thermally conductive filler may be surface-treated or coated to promote dispersion and increase the amount of filler added. Generally, any known surface treatments and coatings, including those based on silanes, titanates, zirconates, aluminates, and organic oxidative chemicals, may be suitable. For powder handling purposes, many fillers are available as polycrystalline granules or aggregates, with or without binders. Some embodiments may include mixtures of particles and granules of various sizes and formulations. While not bound by theory, it is presumed that including a sufficient amount of small particles with appropriate particle sizes improves thermal conductivity between larger particles.

[0068] With respect to small particles, at least 20, 25, 30, 35, 40, 45, or 50 volume percent of the particles have a particle size of 10 micrometers or less. In some embodiments, at least 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, or 60 volume percent of the particles have a particle size of less than 5 micrometers. In some embodiments, at least 10% of the particles have a particle size of less than 1 or 2 micrometers. In some embodiments, at least 20, 25, or 30 volume percent of the particles have a particle size of less than 1 or 2 micrometers. In other embodiments, less than 10 volume percent of the particles have a particle size of less than 1 or 2 micrometers.

[0069] With respect to larger particles, at least 10, 15, 20, 25, or 30 volume percent of the particles have a particle size of 30, 40, or 50 micrometers or larger. In some embodiments, larger particles have a particle size of at least 55, 60, 65, 70, 75, 80, 85, 90, or 100 micrometers. Larger particles typically have a particle size of 200, 190, or 180 micrometers or less. In some embodiments, larger particles have a particle size of 170, 160, 150, or 140 micrometers or less. In some embodiments, larger thermally conductive particles have a particle size of 130, 120, or 110 micrometers or less. In some embodiments, larger thermally conductive particles have a particle size of 100, 90, or 80 micrometers or less. In some embodiments, 5 volume percent of the particles have a particle size greater than 55, 60, 65, 70, 75, 80, 85, 90, or 100 micrometers. In some embodiments, 5% by volume of particles have a particle size greater than 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 166, 170, 175, 180, or 185 micrometers.

[0070] Preferably, the polymer composition or polymerizable composition may contain 10% by weight or more of inorganic fillers having an average particle size of 30 micrometers or more, 40 micrometers or more, or 50 micrometers or more, based on the total weight of the polymer material.

[0071] A combination of small and large particles can be obtained by selecting certain (e.g., commercially available) particles that have at least a bimodal distribution of particle size. A combination of small and large particles can also be obtained by combining two or more (e.g., commercially available) particles that have a normal distribution of particle size but whose median particle sizes are sufficiently different.

[0072] In particular, if the particle combination is obtained by combining particles that have a normal distribution of particle size but with different median particle sizes, the particles further include particles with intermediate particle sizes. Thus, the particles further include particles in the range of greater than 10 to less than 30 micrometers. The sum of small particles (i.e., 10 micrometers or less), large particles (at least 30 micrometers), and intermediate particles is typically 95, 96, 97, 98, 99, or 100% of the thermally conductive particles. The thermally conductive particles may optionally include 1, 2, 3, 4, or 5% of particles with a particle size greater than 200 micrometers (e.g., extra-large).

[0073] The particle size of thermally conductive particles can be determined using dynamic light scattering (DLS).

[0074] In a typical embodiment, particle size refers to the “primary particle diameter,” meaning the diameter of a single (non-aggregated, non-clumped) particle. Primary particles can form “clumps,” i.e., weak associations between primary particles that are held together by charge or polarity and can also be broken down into smaller entities. These weakly bound clumps typically break down during high-energy mixing processes. In some embodiments, particle size may also refer to the particle size of aggregates, i.e., two or more primary particles bound together. Depending on the viscosity and mixing technique, aggregates may break down into smaller entities during mixing.

[0075] In a method for preparing a thermally conductive article having an array of pads (for example, as shown in Figure 7), the method of the second embodiment further includes constructing the array of pads. This may include arranging a plurality of pads in a tile-like array and joining them together.

[0076] In a third embodiment, another thermally conductive article is provided. The thermally conductive article includes a) a pad having first and second oppositely oriented main surfaces and a thickness between them, b) a first thermally conductive skin layer, and c) a second thermally conductive skin layer. The thickness of the pad is formed by a plurality of aligned thermally conductive fibers, at least a portion of which have terminations on the first oppositely oriented main surface and the oppositely oriented second main surface. The thermally conductive fibers have an average diameter of 0.5 micrometers to 500 micrometers. The first thermally conductive skin layer is located on the first main surface of the pad and includes a polymer matrix at least partially embedded in the terminations of at least a portion of the thermally conductive fibers. The second thermally conductive skin layer is located on the second main surface of the pad and includes a polymer matrix at least partially embedded in the terminations of at least a portion of the thermally conductive fibers.

[0077] In a fourth embodiment, another method is provided, which includes a) aligning a plurality of thermally conductive fibers having a first end, length, and a second end facing the opposite direction; b) embedding a thermally conductive polymer material or a thermally conductive polymer material into the first ends of at least a portion of the thermally conductive fibers; and c) drying the polymer material or polymerizing the polymerizable material. The thermally conductive fibers have an average diameter of 0.5 micrometers to 500 micrometers, and are aligned such that at least a portion of the length of the thermally conductive fibers is parallel to each other at an angle of ±20 degrees.

[0078] The following disclosures relate to both the third and fourth aspects.

[0079] Referring to Figure 8, a schematic side view of an exemplary article 8000 is shown. The thermally conductive article 8000 comprises a pad 8100 containing a plurality of aligned thermally conductive fibers 8120. This embodiment also includes an optional binder 8110 positioned between the thermally conductive fibers 8120 and in contact with at least a portion of the aligned thermally conductive fibers 8120. In some embodiments, the binder 8110 is a thermally conductive polymer or composite material. In selected embodiments, the thermally conductive binder 8110 is in the form of a foam.

[0080] Suitable binders and fillers include, but are not limited to, all of the polymers and thermally conductive particulate materials described in detail above for the skin layer in the first embodiment.

[0081] The thermal conductive article 8000 further comprises a first skin layer 8200 attached to the first main surface of the pad 8100. In the embodiment shown in Figure 8, aligned thermal conductive fibers 8220 optionally extend through the first skin layer 8200, resulting in increased heat transport through the thickness (e.g., z-axis) of the thermal conductive article 8000. The first skin layer 8200 further comprises a polymer material 8210, which often results in increased surface contact between the thermal conductive article 8000 and an article to which heat is desired to be a source or destination. In the embodiment shown in Figure 8, the thermal conductive article optionally further comprises a second skin layer 8300. The second skin layer may have the same composition as the first skin layer 8200 or a different composition. Optionally, at least one of the first and second skin layers has a thickness of 0.1 mm or more, 0.2 mm or more, 0.3 mm or more, 0.4 mm or more, 0.5 mm or more, or 0.6 mm or more, and a thickness of 1 mm or less, 0.9 mm or less, 0.8 mm or less, or 0.7 mm or less. Both the first and second skin layers may have the same range of thickness (e.g., 0.1 mm to 1 mm).

[0082] At least one of the first or second skin layer preferably comprises silicone, epoxy, polyether, acrylate, or polybutadiene. In some embodiments, the first skin layer comprises a composite material. Similarly, in some embodiments, the second skin layer comprises a composite material. Suitable thermal conductive particles to be included in the composite material include, for example, all the thermal conductive particles described above in relation to the first embodiment.

[0083] Referring to Figure 9A, a photograph of an exemplary thermally conductive article 9000 prepared according to the present disclosure is shown. The article 9000 comprises an epoxy skin layer 9100 and a plurality of aligned copper fibers 9200 formed in the epoxy skin layer 9100. Figure 9B is a photograph of the side view of the article of Figure 9A. The degree of alignment of the copper fibers 9200 is seen in Figure B. Generally, the copper fibers 9200 are oriented within ±20 degrees relative to one another, with a small number of copper fibers 9200 outside that range. If one or both ends of the fibers are curved, at least 70% or at least 40% of the length of the fibers (e.g., essentially straight) are oriented within ±20 degrees relative to one another. In some embodiments, at least a portion of the thermally conductive fibers has a length inclined at an angle of up to 45 degrees from the first main surface of the thermally conductive article.

[0084] Referring to Figure 10A, a side view photograph of an exemplary thermal conductive article 10,000a prepared according to this disclosure is shown. The copper fiber 1050 provides an article height of about 4 millimeters. Figure 10B is a side view photograph of the article of Figure 10A after compression in a vise, and the compressed thermal conductive article 10,000b has a height of less than 1.5 millimeters. The thermal conductive article 10,000a is compressed by about 60%. One advantage of compressing a thermal conductive article may be to curve at least a portion of the thermal conductive fibers, such as fiber 1060 in Figure 10B. More generally, referring to Figure 10C, the thermal conductive fiber 1050 is curved such that up to 10%, up to 20%, or up to 30% of the length of the fiber end 1060 is away from the principal fiber length. For example, the end of fiber 1060 may form an angle alpha (α) of at least 45 degrees with a plane perpendicular to the principal fiber length. Having curved ends can be advantageous in preventing the thermally conductive article from puncturing the article it is in contact with (e.g., a battery pack). In selected embodiments of the thermally conductive article, at least a portion of the first or second end of the thermally conductive fibers is curved.

[0085] The thermally conductive pad according to this third embodiment preferably provides a continuous heat conduction path from a first main surface to a second main surface facing the opposite direction.

[0086] The total average thickness of the thermally conductive article is not particularly limited and may be 0.25 mm or more, 0.5 mm or more, 1.0 mm or more, 1.5 mm or more, 3 mm or more, 5 mm or more, or 10 mm or more and 20 mm or less, or 15 mm or less.

[0087] Suitable materials for thermally conductive fibers include, but are not limited to, copper, aluminum, steel, aluminum-clad steel, iron, bronze, brass, nickel, chromium, gold, platinum, silver, palladium, rhodium, iridium, ruthenium, osmium, carbon, graphite, aluminum oxide, silicon carbide, boron nitride, ultra-high molecular weight polyethylene, metal-clad polymer fibers, thermally conductive particle-filled polymer fibers, polyethylene, poly(p-phenylene terephthalamide), or combinations thereof. In some embodiments, the thermally conductive fibers include copper, aluminum, steel, nickel, silver, aluminum oxide, silicon nitride, aluminum nitride, boron nitride, silicon carbide, carbon, graphite, ultra-high molecular weight polyethylene, poly(p-phenylene terephthalamide), or combinations thereof.

[0088] In many cases, the thermally conductive fibers have an average diameter of 0.5 micrometers or more, 1 micrometer or more, 2 micrometers or more, 5 micrometers or more, 7 micrometers or more, 10 micrometers or more, 12 micrometers or more, 15 micrometers or more, 20 micrometers or more, 25 micrometers or more, 30 micrometers or more, 40 micrometers or more, 50 micrometers or more, 60 micrometers or more, 70 micrometers or more, 80 micrometers or more, or 90 micrometers or more, and an average diameter of 500 micrometers or less, 400 micrometers or less, 300 micrometers or less, 200 micrometers or less, 150 micrometers or less, 125 micrometers or less, or 100 micrometers or less. In some embodiments, the thermally conductive fibers have an average diameter of 1 micrometer to 250 micrometers.

[0089] A thermally conductive article preferably exhibits a thermal conductivity in the thickness direction (e.g., the thickness of the pad) of more than 1 W / mK, 2 W / mK or more, 3 W / mK or more, 4 W / mK or more, 5 W / mK or more, 6 W / mK or more, 7 W / mK or more, or 8 W / mK or more, and 25 W / mK or less, 22 W / mK or less, 20 W / mK or less, 18 W / mK or less, 16 W / mK or less, 14 W / mK or less, 12 W / mK or less, or 10 W / mK or less.

[0090] In some embodiments, the thermally conductive article preferably exhibits compression of 30% or more, 40% or more, 50% or more, 60% or more, or 70% or more under a maximum pressure of 2 megapascals (MPa), and compression of 80% or less under a maximum pressure of 2 MPa.

[0091] Thermally conductive articles typically exhibit a density of less than 1.00 g / cc per cubic centimeter, 0.90 g / cc or less, 0.80 g / cc or less, 0.70 g / cc or less, 0.60 g / cc or less, 0.50 g / cc or less, 0.40 g / cc or less, 0.30 g / cc or less, or 0.20 g / cc or less, and 0.05 g / cc or greater.

[0092] Figure 12 is a flowchart of an exemplary method for producing a thermally conductive article. More specifically, Figure 12 includes step 1210, aligning a plurality of thermally conductive fibers having first ends, lengths, and oppositely oriented second ends, such that at least a portion of the lengths of the thermally conductive fibers are parallel to each other at ±20 degrees; step 1220, embedding a thermally conductive polymer material or thermally conductive polymer material into the first ends of at least a portion of the thermally conductive fibers; and step 1230, drying the polymer material or polymerizing the polymerizable material. The method optionally includes 1240, embedding a thermally conductive polymer material or thermally conductive polymerizable material into the second ends of at least a portion of the thermally conductive fibers; and 1250, drying the polymer material or polymerizing the polymerizable material.

[0093] Thermally conductive fibers are typically aligned using electrostatic charging, mechanical manipulation, or a combination thereof. Flocking processes are known in the art (e.g., U.S. Patent No. 2,903,376 (Donahare), U.S. Patent No. 6,286,246 (Rachal et al.), U.S. Patent Publication No. 2004 / 117930 (Townley et al.), Journal of Materials Science: Materials in Electronics, Vol. 30, pp. 10233-10243 (2019), Advanced Materials, Vol. 26, pp. 5857-5862 (2014)), and Specialist yarn, woven and fabric structures: Developments and applications, Chapter 12 Flocked Fabrics and Structures, Publisher: Woodhead Publishing, Editor: RH Gong, pp. 287-317). One preferred method for aligning metallic fibers is described in the following examples.

[0094] In a fifth aspect, the disclosure provides a battery module, which includes a thermally conductive article according to either the first or second aspect as a gap filler.

[0095] Figure 13 is a schematic cross-sectional view of an exemplary battery module 200. The battery module 200 includes at least one thermally conductive article 230 (e.g., as described herein) which is placed within a battery trough and acts as a gap filler between a plurality of individual battery cells 210 and a cooling system 250. In the embodiment of Figure 13, an optional system-level thermally conductive article 240 (e.g., as described herein) is also included between the battery trough 260 and the cooling system 250. Furthermore, the battery module 200 optionally includes at least one thermally conductive article 220 (e.g., as described herein) between the individual battery cells 210.

[0096] Other configurations of the battery module are also possible, such as a configuration that includes busbar cooling with TIM material additionally located on top of the battery module, combined with the cooling system. In a simpler version, liquid cooling is not used, thereby eliminating the use of optional system-level thermal conductive articles 240 and cooling systems 250. Furthermore, electrical insulation may be required between the battery cell and the trough, and this insulation can be provided by an electrical insulating coating on the battery cell and / or the trough, or by the use of a thin electrical insulating film.

[0097] Assembled battery subunits may be combined to form further structures. For example, as is known, battery modules may be combined with other elements such as battery control units to form a battery system, such as a battery system used in an electric vehicle. In some embodiments, the thermally conductive articles of this disclosure may be used within the assembly of such a battery system. For example, in some embodiments, the thermally conductive gap filler of this disclosure may be used to mount a battery control unit and assist in cooling.

[0098] Various embodiments are provided, including thermally conductive articles, battery modules, and methods for manufacturing thermally conductive articles.

[0099] In a first embodiment, the disclosure provides a thermally conductive article. The thermally conductive article includes a pad having first and second oppositely oriented main surfaces and a thickness between them. The thickness is formed of a plurality of entangled thermally conductive fibers, at least a portion of which have at least one end on the first oppositely oriented main surface, the oppositely oriented second main surface, or both. The pad is at least partially impregnated with a polymer.

[0100] In a second embodiment, the disclosure provides a thermally conductive article according to the first embodiment, wherein the thermally conductive fibers are metal.

[0101] In a third embodiment, the disclosure provides a thermally conductive article according to the first or second embodiment, wherein the thermally conductive fibers have a thermal conductivity of at least 5 W / mK.

[0102] In a fourth embodiment, the disclosure provides a thermally conductive article according to any of the first to third embodiments, wherein one or both of the first and second oppositely oriented main surfaces have a surface density of at least 5, at least 10, at least 15, or at least 20 fiber ends per square millimeter.

[0103] In a fifth embodiment, the disclosure provides a thermally conductive article according to any of the first to fourth embodiments, having a thickness with a porosity of at least 10%, at least 20%, at least 30%, at least 40%, at least 50%, at least 60%, at least 70%, at least 80%, or at least 90%.

[0104] In the sixth embodiment, the disclosure provides a thermally conductive article according to any of the first to fifth embodiments, wherein the pad is a spiral layer.

[0105] In the seventh embodiment, the disclosure provides a thermally conductive article according to any of the first to fifth embodiments, wherein the pad is striped in a direction perpendicular to the thickness direction of the pad.

[0106] In the eighth embodiment, the disclosure provides a thermally conductive article according to the sixth or seventh embodiment, comprising an array of pads.

[0107] In the ninth embodiment, the disclosure provides a thermally conductive article according to any of the first to eighth embodiments, wherein the thermally conductive fibers include copper, aluminum, steel, nickel, silver, carbon, graphite, aluminum oxide, silicon carbide, ultra-high molecular weight polyethylene, or a combination thereof.

[0108] In the tenth embodiment, the disclosure provides a thermally conductive article according to any of the first to ninth embodiments, wherein the fibers have an average diameter of 0.5 micrometers to 250 micrometers.

[0109] In the eleventh embodiment, the disclosure relates to a polymer having a glass transition temperature (T) of less than 20°C. g The present invention provides a thermally conductive article according to any of the first to tenth embodiments, having ).

[0110] In a twelfth embodiment, the disclosure provides a thermally conductive article according to any of the first to eleventh embodiments, wherein the pad further comprises a plurality of second fibers entangled with thermally conductive fibers.

[0111] In the thirteenth embodiment, the disclosure provides a thermally conductive article according to the twelfth embodiment, wherein the thermally conductive fiber is metal and the second fiber is polymer.

[0112] In a fourteenth embodiment, the disclosure provides a thermally conductive article according to the twelfth or thirteenth embodiment, wherein the polymer fibers comprise at least one of polyolefin fibers, polyester fibers, or polyamide fibers.

[0113] In the fifteenth embodiment, the disclosure provides a thermally conductive article according to any of the first to fourth embodiments, wherein the average thickness of the pad is in the range of 0.1 mm to 50 mm.

[0114] In the sixteenth embodiment, the disclosure provides a thermally conductive article according to any of the first to fifteenth embodiments, exhibiting a thickness-direction conductivity greater than 1 W / mK.

[0115] In the 17th embodiment, the disclosure provides a thermally conductive article according to any of the first to 16th embodiments, exhibiting 50% to 80% compression under a pressure of up to 2 megapascals (MPa).

[0116] In the eighteenth embodiment, the disclosure provides a thermally conductive article according to any of the first to seventeenth embodiments, having a density of less than 1 gram per cubic centimeter (g / cc).

[0117] In the 19th embodiment, the disclosure provides a thermally conductive article according to any of the first to 18th embodiments, wherein the pad provides a continuous heat conduction path from a first main surface to a second main surface.

[0118] In the 20th embodiment, the disclosure provides a thermally conductive article according to any of the first to 19 embodiments, wherein at least a portion of the thermally conductive fibers has terminations on each of the first opposite main surface and the second opposite main surface of the pad.

[0119] In the 21st embodiment, the disclosure provides a thermally conductive article according to the 20th embodiment, wherein at least 25% of the thermally conductive fibers have terminations on each of the first opposite-facing main surface and the second opposite-facing main surface of the pad.

[0120] In the 22nd embodiment, the disclosure provides a thermally conductive article according to any of the 1st to 21st embodiments, further comprising a plurality of thermally conductive particles dispersed within a polymer.

[0121] In the 23rd embodiment, the disclosure provides a thermally conductive article according to any of the first to 22nd embodiments, which is further impregnated with a second polymer.

[0122] In the 24th embodiment, the disclosure provides a thermally conductive article according to any of the first to 23 embodiments, further comprising a first skin layer attached to a first main surface of the pad.

[0123] In the 25th embodiment, the disclosure provides a thermally conductive article according to any of the first to 24 embodiments, further comprising a second skin layer attached to a second main surface of the pad.

[0124] In the 26th embodiment, the disclosure provides a thermally conductive article according to any of the first to 25 embodiments, wherein the polymer is present as a coating on at least a portion of the entangled thermally conductive fibers.

[0125] A 27th embodiment provides a method for producing a thermally conductive article. This method comprises a) obtaining at least one nonwoven web containing a plurality of entangled thermally conductive fibers and having a first main surface and a second main surface facing the opposite direction; b) impregnating the at least one nonwoven web with a polymer composition or a polymerizable composition; and c) drying the polymer composition or polymerizing the polymerizable composition. This method further comprises d1) wrapping the first main surface of the nonwoven web around the second main surface of the nonwoven web to form an elongated spiral member having a first end and a second end facing the opposite side; and e1) thinly cutting a pad from the first end of the elongated spiral member; or d2) bonding together a laminate of a plurality of coated nonwoven webs; and e2) thinly cutting a pad from the first end of the laminate of a plurality of nonwoven webs. Thus, this method forms a thermally conductive article according to the first embodiment.

[0126] In the 28th embodiment, the disclosure provides a method according to the 27th embodiment, wherein the nonwoven web further comprises a plurality of second fibers.

[0127] In the 29th embodiment, the disclosure provides a method according to the 27th or 28th embodiment, wherein the polymer composition or polymerizable composition comprises 2% to 15% by weight of a solid composition based on the total weight of the polymer components, polymerizable components and solvent in the composition.

[0128] In the 30th embodiment, the disclosure provides a method according to any of the 27th to 29th embodiments, further comprising impregnating the entangled thermally conductive fibers with a second polymer prior to step d1).

[0129] In the 31st embodiment, the disclosure provides a method according to any of the 27th to 30th embodiments, further comprising attaching the first skin layer to the first main surface of the pad.

[0130] In the 32nd embodiment, the disclosure provides a method according to any of the 27th to 31st embodiments, further comprising attaching a second skin layer to a second main surface of the pad.

[0131] In the 33rd embodiment, the disclosure provides a method according to any of the 27th to 32nd embodiments, wherein the thermally conductive article is one of the 3rd to 25th embodiments.

[0132] In the 34th embodiment, the disclosure provides a method according to any of the 27th to 32nd embodiments, which includes constructing an array of pads.

[0133] In the 35th embodiment, the disclosure provides a thermally conductive article. The thermally conductive article includes a) a pad having first and second oppositely oriented main surfaces and a thickness between them, b) a first thermally conductive skin layer, and c) a second thermally conductive skin layer. The thickness of the pad is formed of a plurality of aligned thermally conductive fibers, at least a portion of which have terminations on the first oppositely oriented main surface and the oppositely oriented second main surface. The thermally conductive fibers have an average diameter of 0.5 micrometers to 500 micrometers. The first thermally conductive skin layer is located on the first main surface of the pad and includes a polymer matrix at least partially embedded in the terminations of at least a portion of the thermally conductive fibers. The second thermally conductive skin layer is located on the second main surface of the pad and includes a polymer matrix at least partially embedded in the terminations of at least a portion of the thermally conductive fibers.

[0134] In the 36th embodiment, the disclosure provides a thermally conductive article according to the 35th embodiment, wherein at least one of the first skin layer and the second skin layer has a thickness of 0.1 mm to 1 mm.

[0135] In the 37th embodiment, the disclosure provides a thermally conductive article according to the 35th or 36th embodiment, wherein both the first skin layer and the second skin layer have a thickness of 0.1 mm to 1 mm.

[0136] In the 38th embodiment, the disclosure provides a thermally conductive article according to any of the 35th to 37th embodiments, wherein the first skin layer comprises a composite material.

[0137] In the 39th embodiment, the disclosure provides a thermally conductive article according to any of the 35th to 38th embodiments, wherein the second skin layer comprises a composite material.

[0138] In the 40th embodiment, the disclosure provides a thermally conductive article according to any of the 35th to 39th embodiments, wherein at least one of the first or second skin layers comprises silicone, epoxy, polyether, acrylate, or polybutadiene.

[0139] In the 41st embodiment, the disclosure provides a thermally conductive article according to any of the 35th to 40th embodiments, having a total thickness of 0.25 mm to 20 mm.

[0140] In the 42nd embodiment, the disclosure provides a thermally conductive article according to any of the 35th to 41st embodiments, wherein the pad further comprises a thermally conductive binder in contact with at least a portion of aligned thermally conductive fibers.

[0141] In the 43rd embodiment, the disclosure provides a thermally conductive article according to the 42nd embodiment, wherein the thermally conductive binder is in the form of a foam.

[0142] In the 44th embodiment, the disclosure provides a thermally conductive article according to any of the 35th to 43rd embodiments, wherein the thermally conductive fibers include copper, aluminum, steel, nickel, silver, aluminum oxide, silicon nitride, aluminum nitride, boron nitride, silicon carbide, carbon, graphite, ultra-high molecular weight polyethylene, poly(p-phenylene terephthalamide), or a combination thereof.

[0143] In the 45th embodiment, the disclosure provides a thermally conductive article according to any of the 35th to 44th embodiments, wherein the thermally conductive fibers have an average diameter of 1 micrometer to 250 micrometers.

[0144] In the 46th embodiment, the disclosure provides a thermally conductive article according to any of the 35th to 45th embodiments, exhibiting a thickness-direction conductivity greater than 1 W / mK, greater than 2 W / mK, greater than 5 W / mK, or greater than 8 W / mK.

[0145] In the 47th embodiment, the disclosure provides a thermally conductive article according to any of the 35th to 46th embodiments, exhibiting 30% to 80% compression under a pressure of up to 2 megapascals (MPa).

[0146] In the 48th embodiment, the disclosure provides a thermally conductive article according to any of the 35th to 47th embodiments, having a density of less than 1 gram per cubic centimeter (g / cc).

[0147] In the 49th embodiment, the disclosure provides a thermally conductive article according to any of the 35th to 48th embodiments, wherein the pad provides a continuous heat conduction path from a first main surface to a second main surface.

[0148] In the 50th embodiment, the disclosure provides a battery module, which includes a thermally conductive article according to any of the 1st to 26th or 35th to 49th embodiments as a gap filler.

[0149] In a 51st embodiment, the disclosure provides a method for producing a thermally conductive article, comprising: a) aligning a plurality of thermally conductive fibers having a first end, length, and a second end facing the opposite direction; b) embedding a thermally conductive polymer material or a thermally conductive polymer material into the first ends of at least a portion of the thermally conductive fibers; and c) drying the polymer material or polymerizing a polymerizable material. The thermally conductive fibers have an average diameter of 0.5 micrometers to 500 micrometers, and are aligned such that at least a portion of the length of the thermally conductive fibers is parallel to one another at an angle of ±20 degrees.

[0150] In a 52nd embodiment, the disclosure provides a method according to the 51st embodiment, further comprising f) embedding a thermally conductive polymer material or a thermally conductive polymerizable material at a second end of at least a portion of a thermally conductive fiber, and g) drying the polymer material or polymerizing the polymerizable material.

[0151] In a 53rd embodiment, the disclosure provides a method according to the 51st or 52nd embodiment for aligning a plurality of thermally conductive fibers using electrocharging, mechanical manipulation, or a combination thereof.

[0152] In the 54th embodiment, the disclosure provides a method according to any of the 51st to 53rd embodiments, wherein the thermally conductive article is an article according to any of the 35th to 49th embodiments.

[0153] In the 55th embodiment, the disclosure provides a method according to any of the 51st to 54th embodiments, wherein at least a portion of the first or second end of the thermally conductive fiber is curved.

[0154] In the 56th embodiment, the disclosure provides a method according to any of the 51st to 55th embodiments, wherein at least a portion of the thermally conductive fibers has a length inclined at an angle of up to 45 degrees from the first main surface of the thermally conductive article. [Examples]

[0155] Unless otherwise stated or readily apparent from the context, all parts, percentages, ratios, etc., in the examples and elsewhere in this specification are by weight. In this section, the following abbreviations are used: g = gram, in = inch, cm = centimeter, m = meter, mm = millimeter, mil = 1 / 1000th of an inch, wt.% = percentage by weight, min = minute, kN = kilonewton, W = watt, °C = Celsius, K = Kelvin, RPM = revolutions per minute, MPa = megapascal.

[0156] [Table 2]

[0157] Test method Measurement of Effective Thermal Conductivity: Effective thermal conductivity was determined using a Thermal Interface Material Tester (AnalysisTech (Wakefield, MA)) according to the modified procedure of ASTM-D5470. A 33 mm diameter sample was punched from the example and comparative example pads and placed on the bottom plate of the TIM Tester. The top plate was slowly lowered and brought into contact with the top surface of the sample. The top plate was heated until a temperature gradient was established at an average sample temperature of 50°C, and the bottom plate was cooled. Effective thermal conductivity was calculated by dividing the thermal impedance by the sample thickness. Importantly, the reported values ​​include the contact resistance from the interface between each plate and the sample surface.

[0158] Compression Measurement: Compression curves were collected using a test system available from MTS Systems (Eden Prairie, MN, USA) under the trade name CRITERION C43, equipped with a 10kN load cell and a stainless steel compression fixture with a radius of 1 in (2.54 cm). Samples were compressed at a rate of 100% / min. The compressibility of the samples was compared to the stress of the specimen at 80% compression.

[0159] Density measurement: The density of the pad was determined by dividing the mass obtained using an MS204S scale (Mettler Toledo (Columbus, OH)) by the envelope volume calculated from the pad's diameter and height.

[0160] Measurement of porosity: Porosity is approximated by dividing the envelope pad density by the skeleton density of the coated nonwoven web, subtracting that value from 1, and multiplying by 100 to obtain the percentage of voids.

[0161] Example 1 (EX-1): A nonwoven web was prepared using a commercially available RandoWebber (Rando Machine Corporation). In this process, aluminum fibers and polyester fibers were continuously fed into the machine's feed section in an 80:20 weight ratio and mixed using a spiked elevator in the feed section. A vacuum roller drew the fibers from the feed section into a feed mat, which was then transported to the Weber section of the machine. This feed mat was slowly fed into a lickar in rotating at 400 RPM. The lickar in grasped the individual fibers and fed them into an airflow, and the fibers were collected on a perforated drum. The web was then placed in a 146°C oven for a total of 1 minute to melt the polyester and bond the web.

[0162] The nonwoven web was cut into strips approximately 3 in (7.6 cm) x 12 in (30.5 cm). The strips were immersed in an ethyl acetate solution of 3.4% solids acrylate adhesive until saturated. The strips were then removed from the solution, excess liquid was drained from the web, and they were dried at room temperature. The strips were then rolled by hand along their longitudinal direction to form elongated spiral members. A 3 mm thick thermal conductive pad was thinly cut from the elongated spiral member along a plane perpendicular to the cylindrical axis of the spiral member using an electric knife. The porosity was estimated to be 83% to 97%.

[0163] Example 2 (EX-2): EX-2 was prepared in the same manner as described for EX-1, except that the acrylate adhesive was a 2.9% solids ethyl acetate solution. The porosity was estimated to be between 80% and 97%.

[0164] Example 3 (EX-3): EX-3 was prepared in the same manner as described for EX-1, except that the acrylate adhesive was a 4.4% solids ethyl acetate solution. The porosity was estimated to be between 77% and 97%.

[0165] Example 4 (EX-4): EX-4 was prepared in the same manner as described for EX-1, except that copper fiber A and polyester fiber were continuously supplied to the supply unit in a weight ratio of 80:20. The porosity was estimated to be 85% to 97%.

[0166] Example 5 (EX-5): EX-5 was prepared in the same manner as described for EX-1, except that aluminum fibers were continuously supplied to the feed section and the web was not placed in the oven. The porosity was estimated to be 78% to 97%.

[0167] Example 6 (EX-6): EX-6 was prepared in the same manner as described for EX-1, except that copper fiber A was continuously supplied to the supply section and the web was not placed in the oven. The porosity was estimated to be 84% to 97%.

[0168] Comparative Example 1 (CE-1): CE-1 was prepared according to the description of EX-1, except that it was cut from a coated web without rolling a sample for compression and thermal conductivity testing. The web had a thickness of approximately 0.077 in (0.2 cm).

[0169] [Table 3]

[0170] In Examples 7-9 (EX-7-EX-9), thermally conductive articles containing aligned metal fibers were manufactured by forming one side of the fibers onto a substrate layer, as follows: First, copper fibers B were flocked onto a transfer tape (Masking Tape, available from 3M Company (St. Paul, MN 55144 USA)). The flocking process is known in the art (e.g., U.S. Patent No. 6,286,246 (Rachal et al.), U.S. Patent Publication No. 2004 / 117930 (Townley et al.), Journal of Materials Science: Materials in Electronics, Vol. 30, pp. 10233-10243 (2019), Advanced Materials, Vol. 26, pp. 5857-5862 (2014), and U.S. Patent No. 2,903,376 (Donahue)). In this case, the technique used involves flocking the fibers onto the transfer tape using vibration of the transfer tape. Next, the transfer tape and the fibers attached to the transfer tape as a result of flocking were inverted, and the free ends of the fibers were embedded in a curable material ("skin layer"). The skin layer was formed by coating an uncured skin layer of the composition and thickness shown in Table 3 onto the release material. Aligned metal fibers were attached to the uncured skin layer and partially embedded (approximately 5-25% of the total length). The skin layer was then cured to form a solid material that held the fibers after they had separated from the transfer tape surface.

[0171] Examples 10 and 11 (EX-10 and EX-11) were prepared as described for EX-7, with the addition of the following: In EX-10 and EX-11, the coating layer material shown in Table 3 was applied to the exposed ends of the metal fibers on the opposite side of the first skin layer, allowing it to penetrate into the spaces between the fiber ends to about 5-25% of the total length of the fibers. The resulting thermally conductive article comprises three layers, namely two skin layers at least partially penetrated by metal fibers extending from the first skin layer to the second skin layer, the two solid material skin layers defining two main surfaces of the pad, and a core layer containing metal fibers predominantly oriented in the direction between the main surfaces and separated by void spaces (also referred to herein as pore spaces) within the core layer (i.e., the thermally conductive pad), the core layer extending (between the outer layers of the material) to a thickness of about 50-90% of the total length of the metal fibers. In EX-11, the two outer surfaces of the skin layer were hand-polished after curing using 400 grit sandpaper (obtained from 3M Company (St. Paul, MN, USA)) until the fiber ends were clearly visible on both surfaces.

[0172] Example EX-12 was prepared as described for EX-7, and then coated with grease using a step-down converter, thereby filling the remaining spaces between the fibers with heat-dissipating grease while leaving a uniform surface and almost completely filling the voids between the fibers.

[0173] The thermal conductivity of Examples EX-7 to EX-12 was measured according to the procedure described above. The results are recorded in Table 3.

[0174] [Table 4]

[0175] Any further modifications and alterations to this disclosure can be carried out by those skilled in the art without departing from the spirit and scope of this disclosure, and more specifically from the spirit and scope set forth in the appended claims. It will be understood that the aspects of the various embodiments may be interchangeable in whole or in part, or combined with other aspects of the various embodiments. All references, patent documents, or patent applications cited in the above patent application are incorporated herein by reference in their entirety in a consistent manner. In the event of any inconsistency or contradiction between the incorporated portions of the references and this application, the information in the foregoing description shall prevail. The foregoing statements are intended to enable those skilled in the art to practice the disclosure set forth in the claims and should not be construed as limiting the scope of this disclosure, which is defined by the claims and all their equivalents.

Claims

1. A thermally conductive article comprising a pad having first and second oppositely oriented main surfaces and a thickness between them, wherein the thickness is formed of a plurality of entangled thermally conductive fibers, at least a portion of the entangled thermally conductive fibers having at least one end on the first oppositely oriented main surface, the oppositely oriented second main surface, or both, and the pad is at least partially impregnated with a polymer.

2. The thermally conductive article according to claim 1, wherein one or both of the first and second oppositely oriented main surfaces have a surface density of at least 5, at least 10, at least 15, or at least 20 fiber ends per square millimeter.

3. The thermally conductive article according to claim 1 or claim 2, wherein the thickness has a porosity of at least 10%, at least 20%, at least 30%, at least 40%, at least 50%, at least 60%, at least 70%, at least 80%, or at least 90%.

4. The thermal conductive article according to any one of claims 1 to 3, wherein the pad is a spiral layer.

5. The thermal conductive article according to any one of claims 1 to 4, wherein the pad has stripes in a direction perpendicular to the thickness direction of the pad.

6. A thermally conductive article according to claim 4 or 5, comprising an array of pads.

7. The thermally conductive article according to any one of claims 1 to 6, wherein the thermally conductive fibers include copper, aluminum, steel, nickel, silver, carbon, graphite, aluminum oxide, silicon carbide, ultra-high molecular weight polyethylene, or a combination thereof.

8. The polymer has a glass transition temperature (T) of less than 20°C. g A thermally conductive article according to any one of claims 1 to 7, having )

9. The thermal conductive article according to any one of claims 1 to 8, wherein the pad further comprises a plurality of second fibers entangled with the thermal conductive fibers.

10. A thermally conductive article according to any one of claims 1 to 9, which exhibits 50% to 80% compression under a maximum pressure of 2 megapascals (MPa).

11. The thermally conductive article according to any one of claims 1 to 10, wherein the pad provides a continuous heat conduction path from the first main surface to the second main surface.

12. The thermal conductive article according to any one of claims 1 to 11, wherein at least a portion of the thermal conductive fibers has an end on each of the first opposite main surface and the second opposite main surface of the pad.

13. A method for manufacturing a thermally conductive article, a) Obtaining at least one nonwoven web containing a plurality of entangled thermally conductive fibers and having a first main surface and a second main surface facing the opposite direction, b) Impregnating at least one nonwoven web with a polymer composition or polymerizable composition, c) Drying the polymer composition or polymerizing the polymerizable composition, d1) Wrapping the first main surface of the nonwoven web around the second main surface of the nonwoven web to form an elongated spiral member having a first end and a second end on the opposite side, and e1) Cutting a thin pad from the first end of the elongated rotating member, d2) Bonding together a laminate of multiple coated nonwoven webs, and e2) cutting a thin pad from the first end of the laminate of the plurality of nonwoven webs, A method for forming a thermal conductive article comprising a pad having first and second oppositely oriented main surfaces and a thickness between them, wherein the thickness is formed of a plurality of entangled thermal conductive fibers, and at least a portion of the entangled thermal conductive fibers has at least one end on the first oppositely oriented main surface, the oppositely oriented second main surface, or both, and the pad is at least partially impregnated with a polymer.

14. The method according to claim 13, wherein the thermally conductive article is one of the claims described in any one of claims 1 to 12.

15. (a) A pad having first and second opposite main surfaces and a thickness between them, wherein the thickness is formed of a plurality of aligned thermal conductive fibers, at least a portion of the thermal conductive fibers having terminations on each of the first opposite main surface and the second opposite main surface, and the thermal conductive fibers having an average diameter of 0.5 micrometers to 500 micrometers, b) A first thermally conductive skin layer located on the first main surface of the pad, comprising a polymer matrix at least partially embedded in the ends of at least a portion of the thermally conductive fibers, c) A second thermal conductive skin layer located on the second main surface of the pad, comprising a polymer matrix at least partially embedded in the ends of at least a portion of the thermal conductive fibers, Thermally conductive articles, including [the specified element].

16. The thermally conductive article according to claim 15, wherein the first skin layer comprises a composite material.

17. The thermal conductive article according to claim 15 or 16, wherein the pad further comprises a thermal conductive binder in contact with at least a portion of the aligned thermal conductive fibers.

18. The thermally conductive article according to any one of claims 15 to 17, wherein the thermally conductive fibers include copper, aluminum, steel, nickel, silver, aluminum oxide, silicon nitride, aluminum nitride, boron nitride, silicon carbide, carbon, graphite, ultra-high molecular weight polyethylene, poly(p-phenylene terephthalamide), or a combination thereof.

19. A thermally conductive article according to any one of claims 15 to 18, which exhibits 30% to 80% compression under a maximum pressure of 2 megapascals (MPa).

20. A battery module comprising a thermally conductive article as a gap filler according to any one of claims 1 to 12 or 15 to 19.

21. A method for manufacturing a thermally conductive article, a) Aligning a plurality of thermally conductive fibers having a first end, length, and a second end facing the opposite direction, wherein the average diameter of the thermally conductive fibers is between 0.5 micrometers and 500 micrometers, and the fibers are aligned such that at least a portion of the length of the thermally conductive fibers is parallel to each other at an angle of ±20 degrees. b) embedding a thermally conductive polymer material or a thermally conductive polymerizable material in at least a portion of the first end of the thermally conductive fiber, c) Drying the polymer material or polymerizing the polymerizable material, Methods that include...

22. d) embedding a thermally conductive polymer material or a thermally conductive polymerizable material in at least a portion of the second end of the thermally conductive fiber, e) Drying the polymer material or polymerizing the polymerizable material, The method according to claim 21, further comprising:

23. The method according to claim 21 or 22, wherein the plurality of thermally conductive fibers are aligned using electrocharging, mechanical manipulation, or a combination thereof.

24. The method according to any one of claims 21 to 23, wherein at least a portion of the first end, the second end, or both of the thermally conductive fiber is curved.